“Our own Home”: Negotiated Nature in Symra - Jenna Coughlin (Edda)
Abstract This article examines both the pastoral and anti-pastoral tendencies in Ivar Aasen’s Symra by focusing on the depiction of heim. Aasen uses heim to promote a pastoral that runs counter to the bourgeois idea of nature and the rural relationship to it as passive. This pastoral suggests instead that rural people and nature have an active relationship in which humans act in accordance with the limits set by nature. In Symra these limits are portrayed as foundational for orientation in place and for the creation of a secure, moral community. However, there is also an anti-pastoral critique in Symra that insists on a more realistic view of the difficulties associated with rural life and the negative consequences of ignoring nature’s limits.